POLITIK HUKUM DALAM SISTEM PENEGAKAN HUKUM DI INDONESIA - Diana Ningsih , Lis; Suprihatno, Andri; Rosidin, Utang (Gapenas Publisher, 2024)
This research is motivated by the fact that the law enforcement system in Indonesia often faces challenges in achieving justice and legal certainty, which are influenced by the dynamics of legal politics. This research aims to analyse the influence of legal politics on the effectiveness of the law enforcement system in Indonesia. This research applies a normative legal approach with a descriptive analysis method to explore the relationship between legal policy and its implementation. Data was collected through document review, including laws and regulations and related academic literature. The data was also analysed using qualitative data analysis techniques to identify patterns and relationships within the legal system. The results of this study show that legal policy plays a significant role in shaping the direction of law enforcement, both in terms of policy and implementation on the ground. The findings of this study imply that there is a need for harmonisation between legal policy and law enforcement practices in order to achieve more equitable and transparent justice.